Consumer Choice when the Environment is a Variable: The Case of Residential Site Selection - John M. Hartwick (Queen's University, Department of Economics, 1971)
A consumer must decide not only to allocate his income among alternative items but also where to reside.The two decisions are ofcourse linked. On the income side, prices of goods often depend on shipping or transport costs and also one's net disposable income depends on one's out-of-pocket commuting costs; and on the personal utility side, where one's life directly affects the amount of leisure time available after commuting time has been expended. This paper redevelops the analytics of a consumer optimally selecting a site for his residence and shows that the problem of site selection is a special case of a more general problem of a consumer optimally selecting his environment, environment being a more general case of residential site. The point of departure is an attempt to conceptually refurbish Alonso's now classic treatment of residential site selection. It is in the reformulating of Alonso's treatment that the elements of mode selection, and supply and cost of government services are able to be incorporated into a consumer's optimal allocation of income problem.
Keywords: 330